HARNESSING ARTIFICIAL INTELLIGENCE FOR SUSTAINABLE DEVELOPMENT IN UTTARAKHAND: A SECTORAL APPROACH - Vishwajeet Kumar (International Educational Journal of Science and Engineering, 2025)
This study explores the transformative potential of Artificial Intelligence (AI) in fostering sustainable development in Uttarakhand, a Himalayan state facing socio-economic and environmental challenges. By evaluating AI applications across critical sectors agriculture, education, healthcare, disaster management, governance, and tourism the paper demonstrates how AI can drive efficiency, inclusivity, and resilience in a region marked by topographical complexity and rural dominance. The study incorporates real-time data, government reports, and sectoral analysis to assess AI’s impact, while highlighting ethical concerns and infrastructural barriers such as limited internet access (38% in rural areas) and institutional readiness. The paper concludes with strategic recommendations, including AI research centers, open datasets, and targeted capacity-building. It positions AI not just as a technological tool but as a developmental enabler aligned with the United Nations Sustainable Development Goals (SDGs) for 2030.